I ask for some help with this question:

Prove or provide counter example:

If $\sum\limits_{n=1}^\infty na_n$ converges then $\sum\limits_{n=1}^\infty na_{n+1}$ also converges.

I tries this way:

If $\sum\limits_{n=1}^\infty na_n$ converges then $na_n \to 0$, therefore $a_n \to 0$.

There are 3 possible cases:

1) If $a_n >0 $ and $a_n$ is monotonic decreasing sequence then $na_{n+1}<na_n$ and $\sum_{n=1}^\infty na_{n+1}$ converges by Comparison Test.

2) If $a_n >0 $ and $a_n$ is not monotonic decreasing sequence : it is not possible that $a_{n+1}>a_n$ because in this case $a_n \to \infty$, therefore it must be $a_{n+1} \le a_n$ and $\sum_{n=1}^\infty na_{n+1}$ converges by Comparison Test.

3) If $a_n$ is sign-alternating series. There I have a problem to find a solution.


  • $\begingroup$ Yes it does. If $\sum{na_n}$ is convergent, this implies that for all indices greater than $N$, $\{a_i\}$ is a decreasing sequence converging to $0$. Hence, for $m>N, a_m>a_{m+1}$. $\endgroup$ – fierydemon Dec 1 '13 at 12:06
  • $\begingroup$ @AyushKhaitan, I doubt that that is true. $a_i$'s could slightly oscillate. $\endgroup$ – Listing Dec 1 '13 at 12:09
  • $\begingroup$ My statement still stands. $\endgroup$ – fierydemon Dec 1 '13 at 12:11
  • 6
    $\begingroup$ If you rewrite the second sum in the form $\sum_{n=2}^\infty (n-1)a_n$, you see that it is equivalent to determine whether or not $\sum a_n$ must converge. This seems a bit easier to tackle. In particular, if $a_n\ge0$ then the answer is obviouslyl yes, by the comparison principle. $\endgroup$ – Harald Hanche-Olsen Dec 1 '13 at 12:16
  • $\begingroup$ @Macavity If you use such an $a_n$, $\sum_{n=1}^\infty na_n$ won't converge. $\endgroup$ – user10444 Dec 1 '13 at 12:26

Yes. Put $b_n=na_n$, so the question is now (see my comment on the question):

If $\displaystyle\sum_{n=1}^\infty b_n$ converges, does $\displaystyle\sum_{n=1}^\infty\frac{b_n}{n}$ converge?

Let $s_n=\sum_{k=1}^n b_n$. We get (partial summation) $$ \sum_{k=1}^n\frac{b_k}{k} =\sum_{k=1}^n\frac{s_k-s_{k-1}}{k} =\sum_{k=1}^n\Bigl(\frac1k-\frac1{k+1}\Bigr)s_k+\frac{s_n}{n+1} =\sum_{k=1}^n\frac1{k(k+1)}s_k+\frac{s_n}{n+1} $$ which converges as $n\to\infty$, because $s_k$ is bounded, so the sum is absolutely convergent.

  • 7
    $\begingroup$ I do feel a little bad about posting such a complete answer to a homework question, yet it seemed that an antidote was needed to all the bad answers out there. $\endgroup$ – Harald Hanche-Olsen Dec 1 '13 at 12:40

Using the abelian and tauberian theorem seems reasonable. Let

$$f(z)=\sum a_nz^n$$

Now, if

$$\sum n a_n$$

converges, then

$$f'(z) \to \sum n a_n$$

when $z \to 1^{-}$ (abelian theorem). Then


tends to a definite value when $z \to 1^{-}.$ Recall that $a_n=o(1/n)$. The tauberian theorem then asserts that

$$f(z) \to \sum a_n$$

when $z \to 1^{-}$ in such a case, and hence we are done.

  • 2
    $\begingroup$ That is quite clever. $\endgroup$ – Harald Hanche-Olsen Dec 1 '13 at 13:02

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.